Innovation and firm performance of SMEs in food and beverage industry in southern Thailand / Farida Sasha...[et al.] - Sasha, Farida; Ahmad, Noor Hazlina; Mohaidin, Zurina (Universiti Teknologi MARA, Kedah, 2019)
This research intends to analyze the mediating effect of incremental and radical innovation as related to SME’s performance in the context of Food and Beverage industry in southern Thailand. In doing so, the study also examine how innovation is directly effected by entrepreneurial orientation, market orientation and human capital. This line of inquiry is in tandem with Thailand new policy labelled as “Thailand 4.0 ”; an economic strategy directed at pulling Thailand out of the middle income trap by developing a value-based economy that will drive Thailand into the high-income range via innovation agenda. The study conjectures that entrepreneurial orientation, market orientation and human capital have significant positive effects innovation (incremental and radical) and that innovation affect SME performance positively. It utilizes a survey method to test the proposed model. A sample of 351 SMEs in F&B industry in southern Thailand were invited to participate in this study. The model was tested using SEM-PLS. It is anticipated that the findings give SMEs in southern Thailand support in their. The innovative developments originality of this study is found in its effort to prioritize the importance of innovation in the context of F&B industry in Thailand. In such case , the study integrates Resources- Based View (RBV) theory and Strategic Innovation Theory (SIT) as a medium of reaching an extensive a comprehension of innovation practices in SMEs context.